SUBLINGUAL SPECIFIC IMMUNOTHERAPY IN THE TREATMENT OF HAY FEVER CAUSED BY TREE POLLEN IN CHILDREN - I.M. Gaiduk; D.S. Korostovtsev; O.V. Trusova (Педиатрическая фармакология)
The results of the investigation of effectiveness and safety of sublingual allergen specific immunotherapy (slit) with tree pollen mixture for hay fever treatment in children are presented in the article. 42 children 4 to 18 years old with hay fever (allergic rhinoconjunctivitis, pollen asthma) were included in the study. Birch, alder and hazel pollen sensitization was proved by skin prick test (positive in 5 patients and strongly positive in 37). 2 courses of slit out of flowering season were conducted in every child. Total dose of allergen was 43321 ± 73 PNU (3990 to 120 000 PNU) after 1st course of slit, and 93 850 ± 128 PNU (8750 to 249 000 PNU) after 2nd course. Effectiveness of the 1st course of slit was 3,5 points out of 4,0 and of the 2nd course — 3,8 points. Disease remission was registered in 59,5% patients after the 1st course of slit and in 83,3% patients after the 2nd course. Local side effects (tongue and throat itching, nausea and o edema of lips) and systemic side effects (rhinorrhea, eye itching, fatiguability and bronchospasm) of mild severity did not lead to treatment cessation. Slit is highly effective and safe method for hay fever treatment in children.Key words: pollen sensitization, sublingual allergen specific immunotherapy, children.